How Sequential Interactive Processing Within Frontostriatal Loops Supports a Continuum of Habitual to Controlled Processing - O’Reilly, Randall C.; Nair, Ananta; Russin, Jacob L.; Herd, Seth A. (Frontiers in Psychology, 2020)
We address the distinction between habitual / automatic versus goal-directed / controlled behavior, from the perspective of a computational model of the frontostriatal loops that exhibits a continuum of behavior between these poles, as a function of the interactive dynamics among different functionally-specialized brain areas, operating iteratively over multiple sequential steps. This framework blurs the lines between these traditional distinctions in many ways. At an outer loop of decision making / action selection, one must decide at some level to allow habitual actions to proceed. Furthermore, the part of the brain that generates proposed action plans is common across habitual and controlled / goal-directed behavior — instead the key differences are in how many iterations of sequential decision-making are taken, and to what extent various forms of predictive (“model-based’) processes are engaged. At the core of every iterative step in our model, the basal ganglia provides a “model-free” dopamine-trained Go / NoGo evaluation of the entire distributed plan / goal / evaluation / prediction state, which also serves as the fulcrum of serializing otherwise parallel neural processing. Goal-based inputs to the nominally model-free basal ganglia system are among several ways in which the popular model-based vs. model-free framework may not capture the most behaviorally and neurally relevant distinctions in this area.